Research on Entrepreneurial Intention: An Academic Literature Review and Classification - Aqeel Israr; Norashidah Hashim (Paradigms, 2015)
The purpose of this paper is to review the academic literature available in the field of Entrepreneurial Intention (EI), and conduct a content analysis of the same for the purpose of classification and provide a comprehensive bibliography. Emerald full text, online database was searched to review the available literature on EI. The search resulted in only 118 publications where EI was mentioned as the primary research topic. The sample was further refined to only include papers with empirical research in qualitative and quantitative realms. The resultant of the refined sample was 69 research publications, which were classified in to mutually exclusive categories. The content analysis led to classification of literature on the basis of six categories viz. Publication Year, Journal, Research Area, Research Type, Base Theory and Population. The study identifies the history of research on EI and hints towards future research prospects in research in terms of industry, area of study, methodology, type of study, etc. The paper provides a list of field projects accompanied by a comprehensive bibliography that will be useful to both academicians and practitioners for studying existing research as well as for contemplating future research. This may be considered as the basic compilation and classification of available literature in the field of EI.